CMV IN HEMATOPOIETIC STEM CELL TRANSPLANTATION - Rafael de la Camara (Mediterranean Journal of Hematology and Infectious Diseases, 2016)
Due to its negative impact in the outcome of stem cell transplant (SCT) and solid organ transplant patients (SOT) CMV has been called “the troll of transplantation”. One of the greatest advances in the management of SCT has been the introduction of the preemptive strategy. Since its introduction, the incidence of the viremia, as expected, remains unchanged but there has been a marked decline in the incidence of early CMV disease. But in spite of the advances in prevention of CMV disease, CMV is still today an important cause of morbidity and mortality. Late CMV disease is still occurring in a significant proportion of patients and the so-called indirect effects of CMV are causing significant morbidity and mortality. Fortunately, there have been several advances in the development of new antivirals, adoptive immunotherapy and DNA-CMV vaccines that might transform the management of CMV in the near future.